PERKEMBANGAN PENGETAHUAN ANAK USIA DINI MELALUI PERMAINAN KOMPUTER EDUKATIF (Studi Kasus TK Aisyiyah 3 Salatiga) - Yusuf Sulistyo Nugroho (Universitas Muhammadiyah Surakarta, 2011)
Children are currently have no spirit to learn and develop their creativities due to a conventional studying method they received. The research activity aims to know the influences of computer use in children intelligences and creativities. The activity was implemented to demonstrate the educative games. Each participant was given 1 game CD for installation. The result of the activity is analyzed using two types of questionnaire, before and after the socialization. The result indicates that computer technology has a huge affect to help children in knowledge development and intelligences. It can be seen from the comparison analysis of questionnaires which were distributed before and after the socialization.